2023
DOI: 10.36349/easjvms.2023.v05i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Detection of E.coli from Common Respiratory Infections of Poultry in A.P.

Abstract: In the present work a total of 228 pooled nasal swabs, 228 pooled tracheal swabs samples from the ailing birds and 152 pooled tracheal tissues, 152 pooled lung tissues from the dead birds were collected from the 19 suspected poultry farms in A.P. and were labelled farm wise and specimen wise. The DNA was extracted from the samples by using Trizol method. The PCR and SYBR Green real time PCR tests was standardized by targeting 16 s rRNA gene. The study found that 12 farms were found to be positive for E.coli, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the existing study, the PCR method for detection showed an isolated rate reached 28% E. coli, lower than 42.1% and 47.3% recorded by Thopireddy (2023) from the trachea and lung tissue, respectively by PCR. In the present study, the higher percentage recorded in the conventional method rather than the molecular method related to the high sensitivity and specificity of PCR test for diagnosis of E. coli in clinical specimens (Ozbey and Muz, 2006;Tonu et al, 2011;Innis et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…In the existing study, the PCR method for detection showed an isolated rate reached 28% E. coli, lower than 42.1% and 47.3% recorded by Thopireddy (2023) from the trachea and lung tissue, respectively by PCR. In the present study, the higher percentage recorded in the conventional method rather than the molecular method related to the high sensitivity and specificity of PCR test for diagnosis of E. coli in clinical specimens (Ozbey and Muz, 2006;Tonu et al, 2011;Innis et al, 2012).…”
Section: Discussionmentioning
confidence: 83%